Expression Levels of IL-17A, IL-17F, IL-17RA, and IL-17RC in Prostate Cancer with Taking into Account the Histological Grade according to Gleason Scale in Comparison to Benign Prostatic Hyperplasia: In Search of New Therapeutic Options - Marlena Janiczek; Łukasz Szylberg; Paulina Antosik; Anna Kasperska; Andrzej Marszałek (Journal of Immunology Research)
Prostate cancer (PCa) is the second most commonly diagnosed malignant tumor and the fifth leading cause of cancer death in men in the world. The most common types of tumors are adenocarcinomas. Prostate cancer is a slow-growing cancer. The incidence increases with age. Evaluation of proinflammatory factors such as IL-17A, IL-17F, IL-17RA, and IL-17RC expression makes it possible to assess the impact of inflammatory process on progression of PCa. The aim of the study was to retrospectively assess the histological material of PCa divided into few groups using the Gleason score. Studies were carried out on archival tissue material in the form of paraffin blocks of 40 men with PCa after radical prostatectomy. The control group was composed of 10 men with benign prostatic hyperplasia (BPH). The material was obtained by the transurethral resection of the prostate (TURP). Immunohistochemistry was performed on prepared material using specific primary antibodies against IL-17A, IL-17F, IL-17RA, and IL-17RC. Expression of the antibody to be examined using light microscopy and the Remmele-Stegner score (IRS) in cancer staining was then evaluated. Expression of IL-17 RA was not shown in a group of patients with PCa and in the control group. In the group of patients with Gleason score 8 and 9 PCa, the expression of IL-17A was higher compared to that of IL-17F. In addition, in PCa with an increased grade of Gleason scale, a decrease in the expression of the study inflammatory parameters was found. The inflammatory process has an impact on PCa. A study on IL-17 may become a starting point for further research on an attempt to use, for example, immunotherapy in PCa.